1990
DOI: 10.1177/104063879000200307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Radioimmunoprecipitation Assay to Immunoblotting and ELISA for Detection of Antibody to African Swine Fever Virus

Abstract: A radioimmunoprecipitation assay (RIPA) has been developed for detection of antibody to African swine fever virus (ASFV) and compared with the immunoblot assay with regard to sensitivity and specificity. Two hundred seven field sera, obtained from pigs in Spain from different geographic areas between 1975 and 1986, that were positive by ASFV enzyme-linked immunosorbent assay (ELISA) were also analysed by immunoblot assay and RIPA. By serum dilution experiments, the RIPA appeared at least as sensitive as the EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 10 publications
2
38
0
Order By: Relevance
“…The main consequence of this fact is the increase of false-positive results, making the confirmation of the diagnostic results by IB essential (2,6,20). In order to evaluate the ability of the new ELISAs to analyze properly samples of poor quality, 253 field sera were tested, before and after incubation for 1 month at 37°C, using the prescribed test and recombinant assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main consequence of this fact is the increase of false-positive results, making the confirmation of the diagnostic results by IB essential (2,6,20). In order to evaluate the ability of the new ELISAs to analyze properly samples of poor quality, 253 field sera were tested, before and after incubation for 1 month at 37°C, using the prescribed test and recombinant assays.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by the analysis of sera from infected pigs were compared with the results obtained with the ELISA prescribed for international trade (18) and with the results of ELISAs using recombinant proteins (rP-ELISAs) p32 (p32-ELISA) and p54 (p54-ELISA) (p32 and p54 are two of the most antigenic ASFV proteins [2]). …”
mentioning
confidence: 99%
“…Virus infection of MS cells was carried out with Dulbecco's modified Eagle's medium (DMEM) containing 2% swine serum. Virus infection of CV 1 and Vero cells was carried out with DMEM containing 2% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…These OIE-approved tests are based on the use of live virus as the antigen and involve the requirement of level 3 biosafety facilities for the production and handling of the pathogen (16,20,21). The risk associated with the handling of live virus, together with the lack of reliability of the OIE-ELISA for the analysis of poorly preserved samples so often encountered in sera of African origin (1,3), provides the stimulus for the development of alternative and more robust systems for the detection of anti-ASFV antibodies. Indeed, previous studies have demonstrated that recombinant viral proteins can give improved specificity and sensitivity when they are applied to the analysis of European field sera (9,19,22).…”
mentioning
confidence: 99%
“…The radioimmunoprecipitation assay was performed as described (Alcaraz et al, 1990) except that Streptococcus Protein G (Calbiochem) was used instead of Staphylococcus Protein A to obtain binding to horse Igs.…”
Section: Methodsmentioning
confidence: 99%